Incidence and risk factors of pressure injuries in critically ill patients with COVID-19 - Aline de Oliveira Ramalho; Rodrigo Augusto Gonçalves Fonseca; Eliane Mazócoli; Alessandra Marin; Paula Cristina Nogueira (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to analyze pressure injury (PI) incidence and risk factors in patients with COVID-19 admitted to an Intensive Care Unit and characterize the identified PIs. Method: a retrospective cohort study, consisting of 668 patients, carried out between March 2020 and February 2021. Clinical/demographic and PI variables were collected from medical records and electronic database. Data were analyzed using descriptive and inferential statistics. Logistic regression was performed to analyze risk factors for PI. Results: PI incidence was 30.2% (n=202), with the majority located in the sacral region (52.9%) and in stage 1 (39%). Risk factors were age (p<0.001), Diabetes Mellitus (p=0.005), length of stay (p<0.001), immunosuppression (p=0.034), nutritional risk (p=0.015) and mechanical ventilation (p<0.001). Conclusion: PI incidence in critically ill patients with COVID-19 was high.